2005
DOI: 10.1007/s10482-005-9008-z
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus silvicola nov. sp. from nature reserves of Russia and Portugal

Abstract: Nitrate-positive strains of a filobasidiaceous anamorphic yeast related to Cryptococcus cylindricus were isolated from forest litter in a Russian nature reserve and from a lichen in Portuguese one. Mycocinotyping and rDNA sequence analysis revealed that the strains represent a novel species, for which the name Cryptococcus silvicola (type strain VKM Y-2939=CBS 10099) is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The occurrence of cryptic species will also affect biodiversity assessments in a given habitat and therefore studies based only on morphology might underestimate diversity [65] . Indeed, several authors have suggested that next to the application of different media to culture rare species, the exact identification of cryptic diversity by molecular markers is an important factor that will counter underestimation of yeast diversity found in a given area [66] [67] .…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cryptic species will also affect biodiversity assessments in a given habitat and therefore studies based only on morphology might underestimate diversity [65] . Indeed, several authors have suggested that next to the application of different media to culture rare species, the exact identification of cryptic diversity by molecular markers is an important factor that will counter underestimation of yeast diversity found in a given area [66] [67] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most species of the genus produce extracellular starch-like compounds. Species forming the polyphyletic genus Cryptococcus are dispersed in the orders Tremellales, Trichosporonales, Filobasidiales and Cystofilobasidiales (Fell et al , 2000; Golubev et al , 2006).…”
mentioning
confidence: 99%